Pengaruh Pemberian Mesenchymal Stem Cells Wharton’s Jelly terhadap Ekspresi Gen PPAR-γ pada Tikus Alzheimer - Putri, Nabila Priscilla; Ali, Hirowati; Tofrizal, Tofrizal; Darwin, Eryati; Susanti, Restu; Hasmiwati, Hasmiwati (Jurnal Kesehatan Andalas, 2023)
The increased production of beta-amyloid marks Alzheimer's disease. PPAR-γ shows involvement in Alzheimer's disease. PPAR-γ Gene is suspected to reduce beta-amyloid plaques and reduce inflammation and oxidative stress in Alzheimer's disease. Mesenchymal Stem Cells Wharton's Jelly (MSC-WJ) is expected to increase the PPAR-γ Gene expression. Objective: To observed the PPAR-γ Gene expression in Alzheimer's Mice. Methods: The mice are induced using AlCl3 and were given MSC-WJ. This study was an experimental study with a post-test-only control group design on 18 samples of RNA from Alzheimer's mice that were divided into 3 groups. Negative control group (K-), positive control group (K+), and experimented group (P). The mean of PPAR-γ gene expression was obtained by comparing the PPAR-γ gene with the GAPDH gene. This study used semiquantitative methods using ImageJ. Data analysis was used with the Kruskal-Wallis test. It is significant if the value is <0,05. Results: The mean ratio of PPAR-γ gene expression that was obtained in K-, K+, and P were 0.12, 0.06, and 0.08, respectively. There were significant differences between each group, with a p-value of 0,023 (p<0,05). Conclusion: Giving MSC-WJ could increase the PPAR-γ gene expression. Further study using real-time PCR is highly needed to increase the MSC-WJ treatment in patients with Alzheimer's disease.Keywords: Alzheimer disease, MSC-WJ, PPAR- γ